Original compound with anticonvulsant activity in the treatment of alcoholism. (13th April 2021) - Markova, E.; Savkin, I.; Knyazheva, M.; Shushpanova, T.
Abstract : Introduction: Original compound ortho-fluorobenzonal, a barbiturate derivative, is shown to reveal strong anticonvulsant activity by means increasing GABA-mediation. Disturbance of GABA(A) -receptors functions play an essential role in both alcoholism and epilepsy pathogenesis. Objectives: Taking into account the presence of GABA(A)-receptors on the lymphocytes surface and involvement of immune system in alcoholism pathogenesis, we investigated ortho-fluorobenzonal effects on the immune and nervous systems functional activities in mice with chronic alcohol exposure to find new perspective pharmacological substances in the treatment of alcoholism. Methods: (CBAxC57Bl/6) F1 male mice with 6-month 10% ethanol exposure were undergoing intragastric administration of original compound ortho-fluorobenzonal for 10 days. Animal's alcohol consumption, behavior and immune parameters were estimated. Results: It was found that ethanol daily consumption decreased sharply starting from 2 days of ortho-fluorobenzonal administration and led to the cessation of ethanol consumption by the 4 day in mice with chronic alcohol exposure. Pronounced changes in motor and exploratory activities in "open field" test was registered in long-term alcoholized mice after 10- day course ortho-fluorobenzonal administration. The above behavioral changes were recorded against the brain cytokines synthesis modulation. We have shown also the modulation by ortho-fluorobenzonal of immune system functional activity, in particular, significant cellular and humoral immune response stimulation, estimated by the relative number of antibody forming cells and reaction of delayed-type hypersensitivity respectively. Conclusions: Original compound ortho-fluorobenzonal has a positive neuroimmunomodulation effect that manifests itself in the correction of iimmune and behavior disorders caused by the chronic ethanol exposure, therefore, this compound is promising in the therapy of alcoholism Disclosure: No significant relationships.